Development Of Affective Self – Awareness On Stage Of Later Childhood - Ali Farhan, Fouad; Essa Adham, Ali (Opción, 2019)
Affective Self – Awareness in children according with two variables: A . Age (9,10,11) years. B . sex (males/females). 2 – The indication of differ- ences in the development of Affective Self – Awareness for children accord- ing with two variables:: A . Age (9 ,10, 11) years . B. sex (males/females). In order to achieve the aims of the current study ,the researcher adopts of the scale Affective Self – Awareness (Tangney &eaal,1991) This scale comprises (15) stories, scenarios (10) of which are negative, and the other (5) are positive. They have been prepared as a test which has been translated in to the Arabic language. This test has been checked and examined to be a true demonstration of scaling properties, Also this test has been applied to the sample study of (180) respondents of children aged (9,10 ,11) years. The division between males and females was justifiably applied to (60) child per each age involved in this study. The data got from the sample results were statically computed and show the findings: 1.The children of(9,10,11)years have Affective Self – Awareness.2. The sentimental self – consciousness takes continuous developed way not occasionally in life. 3. The way of the Affective Self – Awareness is not influenced by age and sex.